2006
DOI: 10.1302/0301-620x.88b4.17034
|View full text |Cite
|
Sign up to set email alerts
|

Spinal and pelvic parameters in Marfan’s syndrome and their relevance to surgical planning

Abstract: Spinal deformities are a common feature of Marfan's syndrome and can be a significant cause of morbidity. The morphology of the scoliosis associated with this condition was previously described by Sponseller, but no correlation with the pelvic parameters has been seen. We performed a retrospective radiological study of 58 patients with scoliosis, secondary to Marfan's syndrome and related the findings in the thoracolumbar spine to the pelvic parameters, including pelvic version (tilt), pelvic incidence and sac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 12 publications
2
2
0
Order By: Relevance
“…The prevalence of lens subluxation or luxation in our study, 62%, is the average of what is reported, 43,4 whereas the prevalence of fulfilling the major criteria for the skeletal system was 38%; other reports show large variation. 23,24 The involvement of skin and integument is comparable with the highest prevalence published. 23,27,44 Spontaneous pneumothorax has been rare in our cohort, whereas blebs in the lungs were found more often.…”
Section: Ghent Evaluation Of 105 Norwegian Adults S Rand-hendriksen Esupporting
confidence: 61%
See 1 more Smart Citation
“…The prevalence of lens subluxation or luxation in our study, 62%, is the average of what is reported, 43,4 whereas the prevalence of fulfilling the major criteria for the skeletal system was 38%; other reports show large variation. 23,24 The involvement of skin and integument is comparable with the highest prevalence published. 23,27,44 Spontaneous pneumothorax has been rare in our cohort, whereas blebs in the lungs were found more often.…”
Section: Ghent Evaluation Of 105 Norwegian Adults S Rand-hendriksen Esupporting
confidence: 61%
“…23,24 The involvement of skin and integument is comparable with the highest prevalence published. 23,27,44 Spontaneous pneumothorax has been rare in our cohort, whereas blebs in the lungs were found more often. 45 This can partially be explained by different imaging techniques.…”
Section: Ghent Evaluation Of 105 Norwegian Adults S Rand-hendriksen Esupporting
confidence: 61%
“…Manifest osteoporosis may be more frequent than in the general populations, as some studies describe an increased prevalence of decreased bone mineral density. Marked abnormalities in the pelvic values compared with those found in the unaffected population, with increased retroversion of the pelvis, in particular, were found in one study [293].…”
Section: Craniofacial Featuresmentioning
confidence: 79%
“…Thoracolumbar kyphosis may also be a spinal manifestation and also scores one point. Scoliosis affects more than 50% of MFS patients, as defined using the Cobb method that considers an angle of > 10° significant [ 75 , 76 ]. However, the 2010 Ghent nosology suggests that scoliosis in MFS should be defined as an angle of > 20° to increase specificity.…”
Section: Scoliosis and Spinal Deformitymentioning
confidence: 99%